Basic principles of construction of high-quality analytical adaptable control systems for thermal energy processes - G. Т. Kulakou; A. Т. Kulakou (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2021)
The modeling results and industrial tests of a typical automatic control system (ACS) and the proposed invariant cascade ACS are presented. The advantages of structural-parametric optimization methods for creating high-quality control systems for heat-and-power processes have been substantiated. The following algorithm for forming a block diagram of a high-quality invariant cascade SAR is proposed. At the beginning, the structure of the optimal transfer function of the stabilizing regulator is determined as the product of the inverse transfer function of the leading section of the object by a given transfer function of the open system of the internal circuit in the form of an ideal integrating link with one calculated parameter of dynamic tuning, which allows optimally working out both internal disturbances and the task of the stabilizing regulator. Then, the parameters of the dynamic adjustment of the corrective regulator are calculated for optimal processing of the extreme external disturbance. Next, an equivalent external perturbation is isolated without its direct measurement using a complete model of the inertial section of the object. At the same time, the obtained difference between the main adjustable value and the model output is fed to the input of an equivalent external perturbation compensation device implemented in the form of a differentiator, which makes it possible to increase the accuracy and speed of the invariant SAR compared to the standard one. To ensure high quality control over the entire range of load changes, the parameters of the dynamic adjustment of the invariant SAR and the model of the inertial section are adjusted in the load function.